Testing for HIV: concise guidance. - Palfreeman, A; Fisher, M; Ong, E; Wardrope, J; Stewart, E; Castro-Sanchez, E; Peto, T; Rogstad, K; Sheather, J; Gazzard, B; Pillay, D; O'Brien, J; et al. (2009)
HIV is now a treatable medical condition and the majority of those living with the virus remain fit and well on treatment. Despite this a significant number of people in the UK are unaware of their HIV infection and remain at risk to their own health and of passing their virus unwittingly on to others. Late diagnosis is the most important factor associated with HIV-related morbidity and mortality in the U.K. Testing for HIV infection is often not performed due to misconceptions held by healthcare workers even when it is clinically indicated and this contributes to missed or late diagnosis. This article summarises the recommendations from the U.K. national guidelines for HIV testing 2008. The guidelines provide the information needed to enable any clinician to perform an HIV test within good clinical practice and encourage 'normalisation' of HIV testing. The full version is available at www.bhiva.org/cmsl 222621.asp.